The Way Home - Leather S. Sue (Cambridge english readers Level 6)
Modern, original fiction for learners of English. Seven journeys which change lives for ever. A New York fashion buyer returns to her English home. A successful author meets an old friend. A reporter travels to an execution. A lorry driver gives an escaped prisoner a lift. A taxi driver picks up Bruce Lee. A mans love for a tram driver leads him to follow her. And four strangers meet at a motel for the first and last time.